Comparison and evolution of pan evaporation and reference evapotranspiration in the semiarid central pampas region (Semiárida, 2024)
The objective of this study is to examine changes in atmospheric water demand in the central semi-arid Pampas region over the last 30 years through evaporation and reference evapotranspiration (ETo). Data were obtained from the agrometeorological station of the College of Agronomy at UNLPam located in Santa Rosa, La Pampa. Evaporation was measured using an American-type A pan (E-T), and ETo was estimated using the Penman-Monteith equation (ETo-PM) for the period 1988-2019. Results showed that annual E-T ranged from 1850.0 to 2940.0 mm, while annual ETo-PM varied from 1130.0 to 1620.0 mm. The average annual E-T was 2332.7 mm ± 320.8 mm, and the average annual ETo-PM was 1346.4 mm ± 145.8 mm. Despite differences in absolute values, E-T and ETo-PM were directly associated (p
Keywords: atmospheric demand; water use efficiency; evaporation pan coefficient; Penman-Monteith